2019
DOI: 10.1111/jace.16436
|View full text |Cite
|
Sign up to set email alerts
|

Y4.67Si3O13‐based phosphors: Structure, morphology and upconversion luminescence for optical thermometry

Abstract: How to improve the sensitivity of the temperature‐sensing luminescent materials is one of the most important objects currently. In this work, to obtain high sensitivity and learn the corresponding mechanism, the rare earth (RE) ions doped Y4.67Si3O13 (YS) phosphors were developed by solid‐state reaction. The phase purity, structure, morphology and luminescence characteristics were evaluated by XRD, TEM, emission spectra, etc. The change of the optical bandgaps between the host and RE‐doped phosphors was found,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Upconversion (UC) luminescence refers to the conversion of electromagnetic waves from long to short wavelengths through multi‐photon processes where the absorption of infrared (IR) photons leads to visible emission, which has attracted a lot of attention on the bioimaging, 3‐D color display, printing ink, state‐of‐the‐art lighting, solar cell, fingerprint acquisition, anti‐counterfeiting, and so on 1‐7 . Particularly, based on the measurement of temperature‐dependent UC luminescence intensity of two thermally coupled energy levels of trivalent rare earth (RE 3+ ) ions, the non‐contact optical temperature sensor by using the fluorescence intensity ratio (FIR) technique still keeps a research hotspot in recent years owing to its advantages of fast response, high sensitivity and resolution 8‐13 .…”
Section: Introductionmentioning
confidence: 99%
“…Upconversion (UC) luminescence refers to the conversion of electromagnetic waves from long to short wavelengths through multi‐photon processes where the absorption of infrared (IR) photons leads to visible emission, which has attracted a lot of attention on the bioimaging, 3‐D color display, printing ink, state‐of‐the‐art lighting, solar cell, fingerprint acquisition, anti‐counterfeiting, and so on 1‐7 . Particularly, based on the measurement of temperature‐dependent UC luminescence intensity of two thermally coupled energy levels of trivalent rare earth (RE 3+ ) ions, the non‐contact optical temperature sensor by using the fluorescence intensity ratio (FIR) technique still keeps a research hotspot in recent years owing to its advantages of fast response, high sensitivity and resolution 8‐13 .…”
Section: Introductionmentioning
confidence: 99%
“…Many research works have revealed that UC emission intensities can be affected by the temperature, which is the base of application in temperature sensing for UC luminescence materials 57 . The temperature detection based on the FIR of the two thermally coupled bands attributed to the 2 H 11/2 → 4 I 15/2 and 4 S 3/2 → 4 I 15/2 transitions of Er 3+ ion is widely investigated in Yb 3+ and Er 3+ co‐doped systems 58 .…”
Section: Resultsmentioning
confidence: 99%
“…To avoid cross-relaxation between ions and reverse energy transfer due to the high concentration of activator ions, we controlled the concentration of Ho 3+ and Tm 3+ under a low range and kept the ratio between them at 1 : 1, and carried out our experiments based on some ratios between Yb 3+ and Ho 3+ and Tm 3+ that have been reported in the literature. [36][37][38] NaYF 4 : Yb 3+ /Ho 3+ /Tm 3+ nanoparticles were prepared by the solvothermal method, and detailed analysis and study of the crystal structure, microscopic features, energy transfer mechanism, and temperature sensing characteristics of the specimens were carried out through X-ray diffraction (XRD), field emission scanning electron microscopy (SEM) and transient fluorescence spectroscopy. New avenues are explored for new highperformance optical temperature measurement materials.…”
Section: Introductionmentioning
confidence: 99%